2015
DOI: 10.1007/s13277-015-3369-3
|View full text |Cite
|
Sign up to set email alerts
|

miR-124 represses FZD5 to attenuate P-glycoprotein-mediated chemo-resistance in renal cell carcinoma

Abstract: Renal cell carcinoma (RCC) is one of most malignant neoplasms, exhibiting poor responsiveness to the conventional chemo-regime. Abnormal expression of P-glycoprotein (P-gp) has been implicated in the emergence of multiple-drug resistance (MDR) by reducing the accumulation of intracellular chemotherapy drugs. Wnt signaling plays critical roles in renal cancer and is triggered by binding of Wnt ligands to Frizzled (FZD) receptor proteins. miR-124 is a tumor suppressor associated with cancer relapse and MDR, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…miR-124 is a well-recognized tumor suppressor and is epigenetically silenced in various types of cancer including CRC [16,32]. Additionally, it was reported that restoration of miR-124 repressed Frizzled (FZD) 5 to overcome P-gp-mediated multidrug resistance in renal cell carcinoma [33]. Moreover, miR-124 was found to be downregulated in gefitinib-resistant non-small cell lung cancer (NSCLC) cells, and overexpression of miR-124 sensitized gefitinib-resistant cells to gefitinib [34].…”
Section: Discussionmentioning
confidence: 99%
“…miR-124 is a well-recognized tumor suppressor and is epigenetically silenced in various types of cancer including CRC [16,32]. Additionally, it was reported that restoration of miR-124 repressed Frizzled (FZD) 5 to overcome P-gp-mediated multidrug resistance in renal cell carcinoma [33]. Moreover, miR-124 was found to be downregulated in gefitinib-resistant non-small cell lung cancer (NSCLC) cells, and overexpression of miR-124 sensitized gefitinib-resistant cells to gefitinib [34].…”
Section: Discussionmentioning
confidence: 99%
“…Markedly, several studies have shown that miRNAs, such as miR-200c and others, can attenuate the effects of these drug-resistance components (21,22). In addition, miRNAs play a critical role in the drug-resistance of tumor cells and the clinical response to cytotoxic chemotherapy in cancer (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). The inhibition of ABC transporters by miRNAs has been reported in several studies.…”
Section: Discussionmentioning
confidence: 99%
“…It has been elucidated that miR-124 has a decisive and regulatory role in the epithelial phenotype and epithelial to mesenchymal transition (EMT) of breast cancer cells (Liang et al, 2013). In addition, a study revealed that miR-124 was downregulated in RCC (Long, Du, Liu, Li, & He, 2015). Also, another study demonstrated that miR-124 overexpression alleviated renal injury of septic rats (Li, Zhang, Xu, Li, & Li, 2018).…”
mentioning
confidence: 99%